Similarities in the Metabolic Reprogramming of Immune System and Endothelium - Tang, Chu-Yik; Mauro, Claudio (Frontiers in Immunology, 2017)
Cellular metabolism has been known for its role in bioenergetics. In recent years, much light has been shed on the reprogrammable cellular metabolism underlying many vital cellular processes like cell activation, proliferation, and differentiation. Metabolic reprogramming in immune and endothelial cells (ECs) is being studied extensively. These cell compartments are implicated in inflammation and pathogenesis of many diseases but their similarities in metabolic reprogramming have not been analyzed in detail. One of the most notable metabolic reprogramming is the Warburg-like effect, famously described as one of the hallmarks of cancer cells. Immune and endothelial cells can display this phenotype which is characterized by a metabolic switch favoring glycolysis over oxidative phosphorylation (OXPHOS) in aerobic conditions. Though energy-inefficient, aerobic glycolysis confers many benefits to the respiring cells ranging from higher rate of adenosine triphosphate (ATP) production to maintaining redox homeostasis. Chemical and biological regulators either promote or perturb this effect. In this review, nitric oxide (NO), hypoxia-inducible factor (HIF), and AMP-activated protein kinase (AMPK) have been discussed for their common involvement in metabolic reprogramming of both systems. From in vitro and animal studies, various discrepancies exist regarding the effects of these regulators in metabolic switch. However, it is generally accepted that glycolysis favors inflammatory reactions whilst OXPHOS favors anti-inflammatory processes. The reasons for such observation are currently subject of intense studies and not completely understood. Finally, metabolic reprogramming in immune and endothelial cells does not limit to the physiological state in health but can also be observed in pathological states like atherosclerosis and cancer. These new insights provide us with a better understanding of the similarities in metabolic reprogramming across a number of cell types, which could pave the way for future research and possible metabolic-based therapeutics.